Biodegradable polymers in the general waste stream – the issue of recycling with polyethylene packaging materials - Kuciel, S.; Kuźniar, P.; Nykiel, M. (Polimery, 2021)
This paper aims to outline the consequences of unintended mixing of polyolefin and biodegradable materials during recycling. The research was done on blends of high density polyethylene (PE-HD) and two commercial biopolymers intended for packaging applications. The mechanical properties, microstructures, water absorptions and DSC results were analyzed. A significant decrease in the blend properties compared to neat polyethylene and biopolymers is a warning against the poor waste management of biodegradable products.